Graceful - Mass, Wendy, 1967- (Scholastic Press, 2015)
Angelina D'Angelo has left town to see the world. It's now Grace's turn to use her magic to protect the people of Willow Falls, and she is up to the challenge. This is her destiny, after all. But destiny is a funny thing - it doesn't always behave the way you'd expect it to.